(untitled) (Iranian Journal of Kidney Diseases, 2014)
Introduction. Clinical studies of recent years have shown that hyperuricemia is associated with poor outcomes such as cardiovascular mortality and dialysis inadequacy in patients undergoing hemodialysis. Our study investigated the effect of vitamin C supplementation on serum uric acid levels in hemodialysis patients. Materials and Methods. This randomized placebo-controlled trial was conducted on 172 hemodialysis patients. They were randomly divided into the intervention group, to receive 250 mg of vitamin C, three times per week, for 8 weeks, and control groups 1 and 2, to receive placebo injection (saline) and no intervention, respectively. Serum levels of uric acid and creatinine were measured at the start of the study and also after 8 weeks. Results. The mean of serum levels of uric acid was 6.02 ± 1.08 mg/dL (reference range, 2.6 mg/dL to 6 mg/dL). Nearly, half of the patients (46.7%) had a serum level of uric acid greater than 6 mg/dL. The median baseline serum levels of uric acid were 6.2 mg/dL, 5.9 mg/dL, and 6 mg/dL in the intervention, control 1, and control 2 groups, respectively (P = .19). After 2 months, median levels reduced significantly in the vitamin C group to 5.8 mg/dL as compared to 6.4 mg/dL and 6.3 mg/dL in control groups (P = .02). The mean serum creatinine level had no significant changes during the study. Conclusions. Our results demonstrated the existence of a significant negative relationship between vitamin C and serum uric acid levels. Detailed investigations with larger sample sizes and longer-term use of vitamin C are recommended.